Familial Hypercholesterolemia With Coexisting Renovascular Stenosis and Premature Coronary Artery Disease. (14th March 2019) - Mehta, Ojas H; Cameron, James D; Mirzaee, Sam
Abstract: Familial hypercholesterolemia (FH) is a common hereditary lipid disorder associated with substantial risk of premature atherosclerotic cardiovascular disease. We report an interesting newly diagnosed index case of FH in a 31-year-old man who presented to the hospital with an ST-elevated myocardial infarction. He had a background of inadequately treated hypertension and hypercholesterolemia. Further investigations raised the possibility of secondary hypertension after the identification of renal artery stenosis, in addition to other areas of mesenteric arterial stenoses. Our patient's case highlights that early-onset hypertension and hypercholesterolemia in a young individual may be an early manifestation of FH requiring high clinical vigilance and awareness.